Toxic Effects of Acute Water Selenium Exposure on Litopenaeus vannamei: Survival, Physiological Responses, Transcriptome, and Intestinal Microbiota - Xinghui Luo; Jian Chen; Asare Derrick; Gongyu Li; Hongming Wang; Zhihao Xue; Lili Shi; Shuang Zhang (Animals)
Excess selenium (Se) can cause a variety of toxic effects in aquatic animals. However, there is currently a lack of comprehensive studies about the toxicity effects of Se in culture water on shrimp. Based on the 96 h acute toxicity test, which confirmed the 96 h LC50 of Se (Na2SeO3) for Litopenaeus vannamei as 2.69 mg/L, L. vannamei (7.25 ± 0.05 g) were divided into three groups (named CON, S1 and S2) and exposed to Se at concentrations of 0, 0.0269 (0.01 × 96 h LC50), and 0.269 (0.1 × 96 h LC50) mg/L in the water for 72 h, respectively. The toxic effects of Se exposure on L. vannamei were evaluated based on histopathology, oxidative stress, immunity, apoptosis, transcriptional responses, and intestinal microbiota. Results demonstrated that Se exposure induced structural damage to the hepatopancreas of L. vannamei, including hepatocyte vacuolation and necrosis. Compared to the CON group, serum Caspase-3 activity significantly increased, while Bcl-2 activity markedly decreased in the S1 and S2 groups (p < 0.05). No significant differences in Bax activity were observed among groups (p > 0.05). ROS content, as well as activities of SOD, PO, GSH-PX, LYS, AKP, and ACP, exhibited an upward trend under Se exposure (p < 0.05). However, MDA levels showed no significant intergroup differences (p > 0.05). Hemocyte transcriptomic analysis revealed 2103 differentially expressed genes (DEGs) (1294 upregulated, 809 downregulated) in the S2 group compared to CON. GO enrichment indicated significant enrichment of DEGs in cellular processes, binding, and cell components. KEGG pathway analysis highlighted prominent enrichment in ribosome biogenesis in eukaryotes, lysosome, cell cycle, and pancreatic secretion pathways. Intestinal microbiota analysis showed that the Shannon, Simpson, and Pielou indices in the S2 group were significantly lower than those in the CON group (p < 0.05). The relative abundance of Vibrio and Acinetobacter increased significantly in the S2 group, while Enterococcus and Pseudomonas decreased markedly (p < 0.05). In conclusion, Se exposure triggered elevated immune enzyme activities, induced oxidative damage and apoptosis, transcriptional level metabolic disorders, and disrupted intestinal microbiota structure in L. vannamei.